2019
DOI: 10.1016/j.jtcvs.2018.09.136
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and risk of recurrence in patients with esophageal cancer with a pathologic complete response after chemoradiotherapy followed by surgery

Abstract: Objectives: A pathologic complete response in patients with locally advanced esophageal cancer after chemoradiotherapy and surgery is associated with improved overall and disease-free survival. Nevertheless, approximately one third of patients with a pathologic complete response still have a recurrence. The aim of this study was to evaluate risk factors and patterns of recurrence in patients with locally advanced esophageal cancer who achieved a pathologic complete response after chemoradiotherapy and surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 25 publications
6
54
0
Order By: Relevance
“…It has also been demonstrated that a pCR is associated with both increased disease‐free survival and overall survival (OS) 9–13 . This discovery is so valuable that the role of esophagectomy in patients with clinical complete response is still an active subject of research and debate 14,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that a pCR is associated with both increased disease‐free survival and overall survival (OS) 9–13 . This discovery is so valuable that the role of esophagectomy in patients with clinical complete response is still an active subject of research and debate 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] This discovery is so valuable that the role of esophagectomy in patients with clinical complete response is still an active subject of research and debate. 14,15 There is limited data regarding the benefit of lymph node harvest in patients who have a pCR. Retrospective studies with even modest-sized databases have shown that high lymph node counts in patients who have a pCR are no different than those with lower lymph node counts and that the number of lymph nodes sampled in patient who have a pCR was not an independent predictor of survival.…”
mentioning
confidence: 99%
“…In the meantime, there is growing evidence that 5-year survival following resection of esophageal cancer does not equal "cure". Even 5-year survivors of EC seem to have a decreasing but persistent residual risk of postoperative tumor recurrence and death from tumor recurrence up to 10 years from diagnosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Second, few studies have examined risk factors for recurrence after a pathologic complete response. Barbetta and colleagues 5 found that poor tumor differentiation is independently associated with an increased risk of recurrence. Similar to other studies, most (72%) of the recurrences were distant metastases, implicating a need for better systemic tumor control.…”
mentioning
confidence: 99%
“…7 Indeed, despite numerous contemporaneous improvements in patient care, survival for patients with esophageal cancer has improved little during the past several decades. The knowledge that we gain from studies such as that of Barbetta and colleagues 5 should help us to evolve our patient care strategies and make strides against this disease.…”
mentioning
confidence: 99%